2010
DOI: 10.5001/omj.2010.81
|View full text |Cite
|
Sign up to set email alerts
|

Terminalia Arjuna (Roxb.) Modulates Circulatory Antioxidants on 7,12-dimethylbenz(a)anthracene- induced Hamster Buccal Pouch Carcinogenesis

Abstract: The chemopreventive potential of TaBet is probably due to its antilipidperoxidative effect or the presence of some potent bioactive chemopreventive principles in the bark of Terminalia arjuna. The results of the present study indicate that T. arjuna may emerge as a putative chemopreventive agent against oral carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Measurement of plasma lipid peroxidation by-products helps to assess the extent of tissue damage. Extensive studies suggested that lipid peroxides that are generated excessively at the primary site could be transferred through circulation to other organs and provoke damage by propagating lipid peroxidation (Dhanarasu et al, 2010). Increased plasma TBARS observed in the plasma of hamsters treated with DMBA alone is probably due to over production and diffusion of lipid peroxidation by-products from the damaged host tissues with subsequent leakage into plasma (Senthil et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of plasma lipid peroxidation by-products helps to assess the extent of tissue damage. Extensive studies suggested that lipid peroxides that are generated excessively at the primary site could be transferred through circulation to other organs and provoke damage by propagating lipid peroxidation (Dhanarasu et al, 2010). Increased plasma TBARS observed in the plasma of hamsters treated with DMBA alone is probably due to over production and diffusion of lipid peroxidation by-products from the damaged host tissues with subsequent leakage into plasma (Senthil et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The formation of PAH-DNA adducts (DNA binding products), a necessary step in PAH-initiated carcinogenesis, has been widely studied in experimental models and has been documented in human tissues 71 . According to previous studies, several nutrients such as vitamin A 72 73 , C 74 , D 75 76 and E 77 78 protect against the carcinogenic effects of DMBA exposure. The relatively low intake of these nutrients during the ICR-R period could cause a reduced protective effect, which may eventually lead to a relatively high tumor occurrence.…”
Section: Discussionmentioning
confidence: 92%
“…The bark constituents are promising as anti-mutagenic and anti-carcinogenic remedy Needless to say that some species have important phytochemical compounds such as antioxidants, tannins, alkaloids, glycosides, which are useful in the treatment of coronary artery disease, cancer, etc. It is due to the fact that antioxidant contents are associated with the reduction of degenerative disease 3,11,24,25,26 .…”
Section: Terminalia Bellirica Roxbmentioning
confidence: 99%
“…The induction of oxidative stress is associated with cancer and cardiovascular disorders. Thus, it is likely that the high antioxidant contents of many Terminalia species may inhibit cancer formation and/or progression 3,7,9,12,16,25,28,29,30 . 3,5 .…”
Section: Antioxidant and Free Radical Scavengingmentioning
confidence: 99%